Justice court versus social media court - Syarofi, Syarofi (Priviet Social Sciences Journal, 2025)
The development of digital technology, particularly social media, has significantly transformed the dynamics of Indonesia’s criminal justice system. Social media now functions as a public platform that shapes public opinion even before formal legal proceedings commence, giving rise to the phenomenon of "trial by social media." This study analyzes the fundamental differences between formal investigative mechanisms based on the Criminal Procedure Code (KUHAP) and information dissemination mechanisms on social media, as well as their implications for the objectivity, independence, and legitimacy of law enforcement officials. This study employs normative legal methods with qualitative analysis of legislation, legal literature, digital journals, and viral case studies in Indonesia, such as the Vina Cirebon and Mario Dandy cases. The findings indicate that social media rapidly influences public opinion through emotional and simplified narratives, whereas formal justice mechanisms prioritize structured, evidence-based, and procedural processes over emotional narratives. The virality of cases on social media can generate psychological and institutional pressure, threaten investigative objectivity and integrity, and potentially undermine the presumption of innocence. This study highlights the need for digital literacy, transparency in judicial processes, and effective legal communication to ensure that emotional social media narratives do not compromise due process, thereby safeguarding independent, objective, and evidence-based justice for sexual assault victims.